Effect of Aminosilane Nanoparticle Coating on Structural and Magnetic Properties and Cell Viability in Human Cancer Cell Lines - Flores Urquizo, Israel Alejandro; Elizalde Galindo, Jose Trinidad; Garcia Casillas, Perla Elvia; Chapa, Christian; Hernández García, Tomás Constantino; Lugo Loredo, Shadai; Stevens Barrón, Jazmín Cristina (2022)
Magnetic nanoparticle interfaces have aroused great scientific research interest in the biomedical area since the interaction of cells or biomolecules with nanoparticles is determined by the surface properties. Currently, in medical applications, there is a need to study cell interaction and growth, along with changes in structural or magnetic properties, attributed to nanoparticle coatings. In this study the coercive field changes in NixFe3-xO4 nanoparticles (x = 0.0, 0.2, 0.4, 0.6, 0.8, and 1.0) driven by partial or total substitution of Fe2+ content by Ni2+, and by aminosilane coating are evaluated. The nanoparticles are synthesized by the coprecipitation method. The inverse spinel structure is confirmed by X-ray diffraction results and Raman spectra. The aminosilane coating is confirmed by energy-dispersive X-ray spectroscopy and Fourier transform infrared spectroscopy. Dynamic light scattering confirms a mean hydrodynamic size of 10 nm. Scanning electron microscopy micrographs of the uncoated and aminosilane-coated samples show that the particles have a hemispherical shape. The coating increases the coercive field. In addition, uncoated Ni0.2Fe2.8O4 has the highest viability in both MCF7 and HeLa cell lines, and aminosilane coating decreases cell viability. This study contributes to future applications of nanomedicine, such as hyperthermia and drug delivery.